Analisis Penggunaan Reaktor Pembatas Arus Sebagai Pembatas Arus Hubung Singkat Di PT Pulp And Paper - Sukma, Dian Yayan; Shalih, Khairus; Ervianto, Edy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
To keep stability in power supply distribution, PT. Pulp and Paper used loop distribution system in their main substation. This thing caused possibilty of short-circuit current may exceed circuit breaker’s capability. So we need to limiting that short-circuit current not exceed capability of existing circuit breaker. Short-circuit calculation will be done in main substationbus. With keeping possibilty of short-circuit current in secure level, so possibility of shortcircuit current that will happened in load bus will not exceed circuit breaker’s capability. Fromthe calculation of 3 phase short-circuit current IEC 60909 standard using ETAP Power Station 11, noted that 3 phase short-circuit making current at AC 4, AC 11, and AC 15 substation stillexceed circuit breaker’s capabilty . With added current limiting reactors at outgoing TC 40, TC 11, and TC 15 transformer with value of the reaktans eachone 0.37779 ohm, 0.13203 ohm,and 0.21701 ohm, the short-circuit making current at AC 4 substation decrease from 73.014 kA to 62.734 kA, at AC 11 substation decrease from 67.407 kA to 62.421 kA, and at AC 15substation decrease from 70.930 kA to 62.731 kA. Where the lowest voltage at load bus is 19.263 volt.Keywords: short-circuit, current limiting reactor, ETAP 11